Pengaruh Latihan Sirkuit Terhadap Kecepatan dan Kelincahan SSB Putra Harapan Dampyak Kabupaten Tegal - Muhammad Faturrahman (Journal of Physical Activity and Sports (JPAS), 2022)
The rationale for this study is that the training speed of the players is still low, and the agility training is poor because the players do not master the soccer game. Circuit training offers many positive changes to your core skills. The purpose of this study was to determine the effectiveness of SSB speed and agility circuit training Putra Harapan Dampyak, Semarang Regency.This study was conducted using a quantitative approach using the "OneGroups PretestPosttest Design" method. The sample for this study was an SSB Putra Harapan athlete, a Tegal Regency football player. The method used was a sample of 15 players. Collect data using tools used for pre- and post-testing. According to the results of this study, the speed effect of SSB athletes Putra Harapan Dampyak and Tegal Regensi increased after circuit training, with an average pre-workout of 5.80 and an average post-workout of 4.60. After circuit training at SSB Putra Harapan Dampyak, Tegal Regency, the pre-training average was 15.75 and the post-training average was 14.66. This study concluded that there was a significant impact on the provision of speed and agility circuit training to students at the SSB Putra Harapan Dampyak Football School in Tegal Regency. This study can be used as a benchmark when preparing training programs, especially with regard to the speed and agility of football players. Based on these results, circuit training is one of the most effective exercises to increase speed and agility. Additional explorers can use circuit training as an alternative to increase player speed and agility.